Pentaplex PCR for Rapid and Reliable Detection of Virulence-Associated Genes in Avian Pathogenic Escherichia Coli Isolated from Colibacillosis - Yeptho, Atokali H; Ghodasara, Sanjay N; Kalaria, Vinay A; Javia, Bhavesh B; Barad, Dilip B (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The present study was conducted with the aim to characterize Avian Pathogenic Escherichia coli (APEC) isolates from colibacillosis affected chickens and to screen for key virulence-associated genes using a pentaplex PCR assay. A total of 100 tissue samples were collected from chickens diagnosed with colibacillosis during post-mortem examination. Out of these, 77 samples were presumptively identified as E. coli based on cultural and biochemical characteristics. All 77 isolates provisionally identified as E. coli were subsequently confirmed by PCR amplification using genus specific primers targeting the 16S rRNA gene. Further screening of the isolates by pentaplex PCR targeting five APEC-associated virulence genes (iutA, iroN, iss, ompT and hlyF) revealed a high prevalence of these virulence determinants among the E. coli isolates obtained from diseased poultry. The iss and ompT genes were most frequently detected (97.40%), closely followed by iroN and hlyF (96.10%) and iutA (88.31%). Among the isolates, 66 (85.71%) carried all five virulence genes, 9 (11.69%) harbored four genes in various combinations, and only 2 (2.60%) lacked all five genes. These findings substantiate the utility of pentaplex PCR as a rapid, specific, and reliable molecular assay for early identification and differentiation of APEC, thereby supporting prompt intervention and effective control of colibacillosis in poultry production systems.